Energias renováveis e mudanças climáticas - Uma jornada de convergências domésticas e internacionais? Análise da promoção da agenda de transição energética no Brasil - Picchi, Livia (Universidade Federal de São Carlos, 2025)
The presente work comprises a comprehensive approach to analyzing the issue os energy, trough a political perspective. The objective is to investigate and map the international and domestic factors that motivated the formulation of public policies to encourage energy generation from renewable sources in Brazil, as well as the actors and arenas, analyzing the influence of international guidelines and international cooperation agréments that deals with renewable energy and mapping the trajectory of policies enacted on the subject by each presidente, in a period rangin from the 1990s to 2016. To this end, two types of sources are used in research, primary and secondary. The list os primary sources will include a study of a oficial documents prepared and made available by the Brazilian State with the Federal Government as its main focus, as well as publications from international organizations, thus prioriziting multi-method analysis, wich includes historical and documents. It is evident that the dissemination of renewable energy as na important tool for guaranteeing energy security in Brazil i salso shaped, according to aspects that consider the opportunity to confront economic and environmental issues, in order to respond to demand inherent to national development and external projection of Brazil as an important “global player” on the international scene, with a focus on energy transition, in a contexto of the rise of international multilateral efforts, especially since the 1990s, to face demands related to climate change. In addition, in terms of results as the domestic level, it is noted that government agenda relating to the sector is quite diverse and that priorities fluctuate considerably over the Years, with periods of adjustments, as well as significant changes depending on each government. It i salso identified that “non-traditional” renewable energies gain prominence in the PT´s governments, while in the Collor, Itamar and Cardoso governments, priorities are focused almost exclusively on water sources. Furthermore, it is argued that between 1990 and 2016 the energy sector had two distinct policy images, one during the Cardoso governments and the others during the PT governments. From this perspective, the set of elements Around two factors, the 2001-2002 energy crisis, and Lula´s election makes the sector´s image change, as well as enabling the processo f diversification of the Brazilian eletrical matriz and the entry of issues relating to renewable energy on the government agenda, both nationally and internationally.
Renewable energy and climate change - A journey of domestic and international convergences? Analysis of the promotion of the energy transition agenda in Brazil
Keywords: Energias renováveis; Políticas públicas; Mudanças climáticas; Ciência Política e Relações Internacionais; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS